2003
DOI: 10.1590/s0004-282x2003000200012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protein and vitamin B deficiency on the morpho-quantitative aspects of the myenteric plexus of the descending colon of adult rats

Abstract: We carried out this work with the purpose of studying the effects of protein and vitamin B deficiency on the morphologic and quantitative aspects of the myenteric plexus of the descending colon of adult Rattus norvegicus. Twenty-eight rats were divided in two groups, one of them receiving chow with 22% protein level (control) and the other fed with chow having 8% protein level without vitamin B supplementation, during 120 days. Whole-mounts of the descending colon were prepared and stained with Giemsa, NADH-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
10

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 15 publications
0
15
0
10
Order By: Relevance
“…The use of animal models in investigations of food deficiency employing known and controlled diets has the advantage of increasing the knowledge about several aspects of human malnutrition (Enwonwu & Sreebny, 1970). Among these models, the rat has been used the most (Mello et al, 1995;Torrejais et al, 1995;Natali and Miranda-Neto, 1996;Sant'Ana et al, 1997;Meilus et al, 1998;Miranda-Neto et al, 1999;Natali et al, 2000;Sant'Ana et al, 2001;Castelucci et al, 2002;Araújo et al, 2003;Brandão et al, 2003;Natali et al, 2003;Mello et al, 2004). It is considered a good model for nutritional research due to its reduced size, reproductive behavior and adaptability to several diets (NRC, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The use of animal models in investigations of food deficiency employing known and controlled diets has the advantage of increasing the knowledge about several aspects of human malnutrition (Enwonwu & Sreebny, 1970). Among these models, the rat has been used the most (Mello et al, 1995;Torrejais et al, 1995;Natali and Miranda-Neto, 1996;Sant'Ana et al, 1997;Meilus et al, 1998;Miranda-Neto et al, 1999;Natali et al, 2000;Sant'Ana et al, 2001;Castelucci et al, 2002;Araújo et al, 2003;Brandão et al, 2003;Natali et al, 2003;Mello et al, 2004). It is considered a good model for nutritional research due to its reduced size, reproductive behavior and adaptability to several diets (NRC, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Desta forma, os resultados de atrofia dos neurônios NADHdiaforase positivos constatados neste estudo possivelmente seja uma tentativa de manter o metabolismo dos neurônios do plexo mientérico em equilíbrio, uma vez que essa técnica possibilita visualizar neurônios com metabolismo neuronal mais ativo (MIRANDA-NETO et al, 2001), já que a NADH-diaforase é uma enzima mitocondrial (GABELLA, 1969). Azevedo et al (2007), com o mesmo modelo experimental deste estudo, avaliaram a morfometria da parede intestinal do íleo e observaram redução da espessura da parede total, da túnica muscular e da túnica mucosa. Essa atrofia associada com o aumento da população marcada pela NADHdiaforase (MOREIRA et al, 2008) pode corroborar na compreensão da atrofia neuronal evidenciada pela mesma técnica verificada neste estudo, pois a redução da parede intestinal associada ao aumento da marcação neuronal, possivelmente fez com que esses neurônios ficassem menores, no intuito de se ajustarem às necessidades fisiológicas do animal.…”
Section: Resultsunclassified
“…This result can be explained by the lower supply of nutrients caused by FR, such as a reduced availability of amino acids, which can affect protein synthesis in intestinal muscles and support the occurrence of muscle atrophy. Another factor that could explain this result is an increase in protein degradation in this muscle to provide endogenous amino acids and offset the low consumption of these molecules through the diet (Araújo et al 2003). This may make endogenous amino acids available to tissues (e.g., mucosa and nerve cells) with an increased need for protein synthesis before the nutritional condition imposed.…”
Section: Discussionmentioning
confidence: 99%
“…A low-protein diet given to animals at different stages of development (e.g., gestation, lactation, and adulthood) may lead to reduced intestinal size, resulting in a higher concentration of neurons per area in segments of the small intestine (Torrejais et al 1995, Natali et al 2003 and colon (Leite-Mello et al 1997, Sant'Ana et al 1997, Castelucci et al 2002, Araújo et al 2003, Hermes et al 2008a. In the present study, we cannot attribute the intestinal reduction to the higher number of neurons observed in the FR animals compared with normally fed animals because the quantification of these cells was performed per myenteric ganglion and not per intestinal area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation